The standardization of clinical ethics consultation and technique’s “long encirclement” of humanity: a response to Brummett and Muaygil - Parks, Benjamin N.; Mason, Jordan (Philosophy, ethics, and humanities in medicine : PEHM, 2021)
In their recent article, Brummett and Muaygil reject Bishop et al.’s framing of the debate over standardization in clinical ethics consultation (CEC) “as one between pro-credentialing procedural and anti-credentialing phenomenological,” claiming that this framing “amounts to a false dichotomy between two extreme approaches to CEC.” Instead of accepting proceduralism and phenomenology as a binary, Brummett and Muaygil propose that these two views should be seen as the extreme ends of a spectrum upon which CEC should be done. However, as evidenced by several inconsistencies within their article, they have failed to fully appreciate the concern animating Bishop et al.’s proposal. Additionally, because of this failure, they do not seem to realize that credentialing ethicists for CEC will only create different problems in Saudi Arabia even as it possibly solves some of the current problems they identify. In this commentary, we highlight and clarify Brummet and Muaygil’s five misunderstandings of Bishop et al. This leads us to conclude that while they claim to be advocating a middle way between proceduralism and phenomenology, in fact they would like for us to standardize another proceduralism, albeit one that incorporates some of the “qualitative” values of American bioethics.